Interculturalidade e aprendizagem de línguas: relatos de experiências de imersão - Santos, Luana Cristina de Oliveira (2021)
This study aims to investigate and comprehend the experience of some exchange students, specifically: (a) in which way the learning of an additional language by immersion happened, (b) for the collaborators, living in the country in which the goal language is spoken helped the learning of this language and (c) if there are clues that the collaborators developed intercultural competence. Joined this study, five Brazilian exchange students who answered a questionary about their experience in the period of international academic mobility. The elements of the qualitative research were used for the collection and analysis of the data. The theory in which the interpretations were based, overhang in the perspectives of teaching-learning of Leffa and Irala (2014), Leffa (2016), Giraldello e Tedesco (2016), of autonomy, agency and strategy, as highlighted by Jordão (2010), Mota (2017), Easternarck (2017), Ludwig and Ferreira (2017), about learning of languages by immersion, in Figueiredo (2012), Savage e Hughes (2014), Kramsch (2017), interculturality in the teaching-learning of languages in Figueredo (2010), Figueiredo (2012, 2019), Siqueira and Barros (2013), Dutra e Penna (2018), Dutra (2019). The discussion about the functional systemic linguistic, the context of culture and the system of evaluativeness was based in Barbara and Macedo (2009), Almeida (2010), Fuzer and Cabral (2014) and Hood (2019). The analysis of the data reveals that the collaborators, when portraying how the learning of additional language was, mentioned the use of learning strategies of the following types: cognitive, compensations, metacognitives and mainly socioaffective that allowed the leaning of the language by the students through collaboration and interaction with other individuals. Furthermore, when mentioning about how living in the learned goal language country contributed for the learning, they mentioned mainly factors as culture and interaction and lastly, among the five clues of intercultural competence defined by Byram (1997), were identified: curiosity, knowledge, interaction and discovering abilities and cultural-critical/ political education consciousness. By the results of this study, it is possible to infer that in the exchange experience agentives and intercultural speakers are formed. Therefore, this paper valued the international experience as social as educationally.